Profiling Heparan Sulfate‐Heavy Metal Ions Interaction Using Electrochemical Techniques. Issue 55 (18th August 2022) - Shitrit, Ariel; Mardhekar, Sandhya; Alshanski, Israel; Jain, Prashant; Raigawali, Rakesh; Shanthamurthy, Chethan D.; Kikkeri, Raghavendra; Yitzchaik, Shlomo; Hurevich, Mattan
Abstract: Heparan sulfate glycosaminoglycans provides extracellular matrix defense against heavy metals cytotoxicity. Identifying the precise glycan sequences that bind a particular heavy metal ion is a key for understanding those interactions. Here, electrochemical and surface characterization techniques were used to elucidate the relation between the glycans structural motifs, uronic acid stereochemistry, and sulfation regiochemistry to heavy metal ions binding. A divergent strategy was employed to access a small library of structurally well‐defined tetrasaccharides analogs with different sulfation patterns and uronic acid compositions. These tetrasaccharides were electrochemically grafted onto glassy carbon electrodes and their response to heavy metal ions was monitored by electrochemical impedance spectroscopy. Key differences in the binding of Hg(II), Cd(II), and Pb(II) were associated with a combination of the uronic acid type and the sulfation pattern. Abstract : A new way to look : The effect of glycosaminoglycans structural properties on their interaction with heavy‐metal ions is enigmatic because of the limited accessibility to structurally well‐defined glycans and the absence of suitable analytical techniques. The study shows that electrochemical analyses and surface science tools provide valuable insight into the effect of structural components on heparan sulfate and lead(II), cadmium(II) and mercury(II) ions interactions.